Cabbage Waste as Raw Material for Biogas Production with Water and Chicken Manure Activator - Haesti Sembiring; Riyanto Suprawihadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cabbage is the third largest commodity in North Sumatra after chili and tomatoes. in 2015 which was 70,730 tons, in 2016 the amount of cabbage production was 92,551 tons and in 2017 the amount of cabbage production was 98,325 tons, it can be seen that the trend is increasing every year. Cabbage waste that is wasted and not utilized can cause pollution and environmental pollution